Associations Between Household Pesticide Exposure, Smoking and Hypertension - Chen, Haiyan; Liang, Xiaohua; Chen, Li; Zuo, Lei; Chen, Kuncai; Wei, Yuehong; Chen, Shouyi; Hao, Guang (Frontiers in Public Health, 2022)
This study aims to investigate the association between household pesticide exposure and hypertension risk, and to determine whether smoking plays a role in this association. We used data from the National Health and Nutrition Examination Survey (NHANES) for the years 1999–2014, including a total of 32,309 U.S. adult participants who were 20 years or older. Smoking status and pesticide exposure were self-reported. Blood pressure was measured by trained personnel using a mercury sphygmomanometer, according to a standardized protocol. We observed an increased risk of hypertension (OR [odds ratio] = 1.10, 95% confidence intervals [CI]: 1.01–1.18) in participants with exposure to household pesticides. Moreover, a significant interaction between smoking status and pesticide exposure on hypertension was observed (P = 0.022). Stratified analysis showed that household pesticide exposure was associated with a 29% higher risk of hypertension (OR = 1.29, 95% CI: 1.08–1.53) in smokers. However, for nonsmokers, this association was not significant. Similar trends were found for systolic and diastolic blood pressures. In addtion, we investigated the associations between pesticide metabolites in urine/serum and hypertension, and found that several metabolites of dioxins, furans, and coplanar polychlorinated biphenyls were significantly associated with a higher risk of hypertension. This study suggests that household pesticide exposure is associated with an elevated risk of hypertension. For the first time, we report that smoking may accentuate the effect of pesticide exposure on hypertension.